Oscillations for Neutral Functional Differential Equations - Fatima N. Ahmed; Rokiah R. Ahmad; Ummul K. S. Din; Mohd S. M. Noorani (The Scientific World Journal)
We will consider a class of neutral functional differential equations. Some infinite integral conditions for the oscillation of all solutions are derived. Our results extend and improve some of the previous results in the literature.